2011
DOI: 10.1007/s00405-011-1765-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the open rhinoplasty incision decrease nasal projection?

Abstract: To evaluate the effects of open rhinoplasty incisions on tip projection using digitized photographs. Thirty-one patients, who underwent open technique rhinoplasty were prospectively included in the study. The lateral aspect photographs were taken before the operations. Following midcolumellar incision septal elevation was done until septal cartilage was shown. After replacing the skin totally back and suturing midcolumellar incision, the intraoperative photographs were taken. The projection indexes were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…In several studies, changes in nasal tip projection were reported after conventional septoplasty maneuvers or the basic stages of open and closed rhinoplasty techniques, such as incision, cephalic trimming, dome suturing, or grafting. 1,[4][5][6][7][8] However, no study has reported the effects on nasal aesthetic character of open-approach extracorpereal septoplasty (OAES) without simultaneous rhinoplasty. The present study focuses on the objective changes to nasal tip projection and rotation after OAES without simultaneous rhinoplasty.…”
mentioning
confidence: 99%
“…In several studies, changes in nasal tip projection were reported after conventional septoplasty maneuvers or the basic stages of open and closed rhinoplasty techniques, such as incision, cephalic trimming, dome suturing, or grafting. 1,[4][5][6][7][8] However, no study has reported the effects on nasal aesthetic character of open-approach extracorpereal septoplasty (OAES) without simultaneous rhinoplasty. The present study focuses on the objective changes to nasal tip projection and rotation after OAES without simultaneous rhinoplasty.…”
mentioning
confidence: 99%
“…In septorhinoplasty, obtaining good outcomes is harder than the procedure itself [ 3 ]. Thus, different techniques developed for this purpose aimed preventing early and late complications [ 2 ]. While it is necessary to reconstruct the nose such that it fits the face of the patient, functionality of the nose is the primary goal of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There are several complications associated with septorhinoplasty. In order to prevent complications, surgeon must choose the most suitable approach for the patient [ 1 , 2 ]. Early complications occur on the first 30 day period postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Ces différentes actions aboutissent à une « libération » de l'arche alaire qui reculera d'une façon plus ou moins importante selon la longueur et la résistance des crus mésiales et des crus latérales. Il faut aussi garder à l'esprit que la voie d'abord externe entraîne une perte de projection de la pointe plus importante que la voie endonasale et que la cicatrisation de la peau tendra toujours à faire reculer la pointe du nez [16].…”
Section: Stratégie Thérapeutiqueunclassified